Analisis Pelayanan Personil SPKT ( Sentra Pelayanan Kepolisian Terpadu) Polres Payakumbuh - Ikhbal, Mohammad; Suryanto, Dasep (Benefit: Journal of Bussiness, Economics, and Finance, 2025)
The Payakumbuh Police Integrated Police Service Centre (SPKT) plays a crucial role in ensuring fast, efficient, and professional public services. Despite innovations such as the use of information technology, the construction of SPKT rooms, and the launch of SPKT Mobile, obstacles remain, including limited personnel, suboptimal facilities, and slow complaint responses. This study aims to analyse the SPKT (Integrated Police Service Centre) personnel services at the Payakumbuh Police. The research method employed a qualitative approach with purposive sampling of 15 informants, analysed using the Miles and Huberman interactive model. The results showed relatively good efficiency through time management, information system utilisation, and personnel training. Document processing effectiveness was relatively fast, but report responses, particularly at night, were relatively slow. Service quality and public satisfaction remained low, while compliance with standard operating procedures (SOPs) was lacking due to minimal training and supervision. It is recommended to improve personnel competency, accelerate response times, digitise services, and conduct routine supervision.